Deutsch-polnische Äquivalenz aus der Sicht der Textstruktur - Gaca, Alicja (Studia Germanica Posnaniensia, 2018)
In the article the author discussed the problem of coherence of text in German and Polish, namely the principle of indications on the line of the text. The author established a number of exponents (indicators) of the so called reference of the text whose interpretation has been extended with the aspect of the so called isotopy of the text. The established types of equivalence give a picture of regularity in the structure of the text and point to the systems possibilities and restrictions in the field of the so called language usage in both languages.